Navigating Uncertainty: A Thematic Literature Exploration of Resource-Based Competitive Advantage During The Covid-19 Pandemic - Susanto, Putu Chris; Wibowo, Martino (Journal of Management and Business Environment (JMBE), 2024)
Resource-based competitive advantage has received considerable attention as a research topic in the field of strategic management and entrepreneurship. However, despite the emergence of RBV-related studies on competitive advantage during the uncertain times brought about by the COVID-19 pandemic, a significant gap persists in understanding how firms can effectively navigate the complexities of this era. This article addresses this gap by conducting a comprehensive literature study that reviewed 16 academic papers published during 2021-2022, drawn using the rigorous SPIDER approach from reputable journals in selected databases. While prior research has explored the RBV in the context of competitive advantage, this study innovatively focuses on the unprecedented challenges posed by the pandemic and the accompanying VUCA environment. Following a content analysis, thematic analysis revealed six distinct streams of themes related to RBV and sustainable competitive advantage in this context—i.e., dynamic capability, innovation, intangible resources, organizational resilience, knowledge management, and circular economy. These themes and their intricate interplay represent an emerging trend of studies on competitive advantage from the RBV perspective, offering a novel lens through which to examine the impact of unprecedented disruptions like COVID-19. The managerial implication relates to how firms can identify the sources of competitive advantage, and how to sustain or even further expand firms’ competitive advantage following the global pandemic.